Republic of Armenia : Fifth Review Under the Poverty Reduction and Growth Facility and Request for Extension of the Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper examines Armenia's Fifth Review Under the Poverty Reduction and Growth Facility (PRGF) and Request for Extension of the Arrangement. Performance under the PRGF-supported program since mid-2003 has been satisfactory: the authorities met all quantitative targets and implemented most of the envisaged structural measures. Tax revenue collection was somewhat disappointing in 2003, although it has improved in early 2004. Future growth in Armenia will increasingly depend on the ability of the banking system to mobilize and allocate domestic savings.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet